The contender Andrew Cuomo, a biography - Shnayerson, Michael 1954- (Grand Central Publ., 2015)
Examines the life and career of the New York attorney general and governor
Includes bibliographical references and index
The high point -- The men in the family -- From Andy to Andrew -- A loyalty like heat -- The enforcer -- A cause to embrace -- In search of a killing -- Cuomolot -- Waterloo in White Plains -- Mr. Cuomo goes to Washington -- Rise to power -- Mr. Secretary -- A nemesis to contend with -- A last chance for change -- Running into the ground -- Hitting bottom -- Attorney General with a vengeance -- Managing the meltdown -- Man of the people -- Going for the govenor -- A state in need of saving -- Like Midas -- Making enemies -- The great allure of gaming -- Guns and butter -- Scandalmania -- Less is Moreland -- Starting again -- Full circle
Keywords: Cuomo, Andrew Mark / 1957-; Cuomo, Andrew Mark -- 1957-; Governors / New York (State) / Biography; Cabinet officers / United States / Biography; HISTORY / Americas (North, Central, South, West Indies); Governors; Politik; New York (State) / Politics and government / 1951-; New York (State); USA; Biografie